MENGUATKAN MAKNA DAN FUNGSI BAHASA SUGESTI GURU BK DALAM MENYELESAIKAN MASALAH KENAKALAN SISWA SMA DENGAN TEKNIK VARIASI KALIMAT - Ardial Janna Julismaini; Paulina, Yanti; Dewi Kusumaningsi; Ajat Manjato; Loliek Kania Atmaja (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Teen delinquency is a crucial phenomenon that continues to grow up to the present. Therefore, efforts to handle this issue have become extremely urgent. In link with this, this study aims to explore how guidance and counseling teachers (BK) can enhance the effectiveness of their interventions in dealing with student delinquency at Muhammadiyah 4 High School in Bengkulu City through sentence variation techniques in suggestive language. The meaning and function of the figurative language are also explored and analyzed in-depth through the interactive analysis technique. A case study research model with a qualitative descriptive method was chosen to understand the subjects and objects studied deeply. Through observation and interview techniques, data were collected and analyzed using the interactive analysis technique of Miles & Huberman to understand the meaning and function of the suggestive language used by BK teachers to resolve teenage delinquency. The study results reveal two patterns of sentence variation in suggestion language: praising and motivational sentences. Keywords: Register, Meaning and Functions of Language, Suggestion, Student Delinquency, Sentence Variation Techniques.